The role of gender and training age in shaping physical characteristics of volleyball players: A comparative analysis - Negi, Geeta; Sharma, Lalit; Singh, Meenakshi; Goel, Komal (Scientific Journal of Sport and Performance, 2024)
High levels of athletics and fitness—including strength, power, speed, agility, coordination, and stamina—are necessary for volleyball. While power is needed for force generation, speed is needed for rapid movements, agility is needed for abrupt direction changes, coordination is needed for body control, and stamina is needed for sustained performance, strength is needed for high leaps and ball striking. A lack of these elements might provide difficulties for the sport. The physical characteristics of volleyball players who are male and female, as well as those who practice at different ages, were compared in this study. A minimum of one year of training age was required for the selection of 312 players from Delhi, of which 144 were female and 168 were male. To evaluate differences, a two-way MANOVA was employed. With more type 2 muscular fibers, longer legs, and larger muscles, male athletes had an edge in speed, core strength, and leg muscle endurance. Performance in these areas was also influenced by years of training. The athletes that played the most got the highest results in terms of arm, core, leg muscular endurance and speed as well as reaction time. The overall score of the participants was impacted by the fact that male players advanced the fastest, while female players gained more gradually.